2013
DOI: 10.1177/216507991306100505
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Cigarette Smoking and Occupational Exposures on Lung Function

Abstract: Workers in the rubber industry are exposed to pulmonary health hazards. The main purpose of this study was to assess the combined effect of cigarette smoking and occupational exposures on lung function. The exposed group consisted of tire manufacturing workers in production units and the non-exposed group included executives from the same factory. The researchers calculated the synergy index (SI) to determine the combined effect of exposures to cigarette smoke and pulmonary health hazards on lung function. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Health Hazard Evaluation Report 2016-0227-3364 Korn el al 1978;Weeks et al 1981a;Weeks et al 1981b;Bascom et al 1988;Tarlo 1992;Zuskin et al 1996;Kato and Leki 2005;Neghab et al 2007;Akca et al 2011;Neghab et al 2011;Attarchi et al 2013]. A prospective cohort study by Lednar et al followed a cohort of actively employed rubber workers over 10 years and reported a higher rate of pulmonary disability among workers in extrusion and curing process work areas compared with a control group [Lednar et al 1977].…”
Section: Medical Surveymentioning
confidence: 99%
See 4 more Smart Citations
“…Health Hazard Evaluation Report 2016-0227-3364 Korn el al 1978;Weeks et al 1981a;Weeks et al 1981b;Bascom et al 1988;Tarlo 1992;Zuskin et al 1996;Kato and Leki 2005;Neghab et al 2007;Akca et al 2011;Neghab et al 2011;Attarchi et al 2013]. A prospective cohort study by Lednar et al followed a cohort of actively employed rubber workers over 10 years and reported a higher rate of pulmonary disability among workers in extrusion and curing process work areas compared with a control group [Lednar et al 1977].…”
Section: Medical Surveymentioning
confidence: 99%
“…A prospective cohort study by Lednar et al followed a cohort of actively employed rubber workers over 10 years and reported a higher rate of pulmonary disability among workers in extrusion and curing process work areas compared with a control group [Lednar et al 1977]. Furthermore, a rubber manufacturing study by Attarchi et al, which reported significantly higher prevalence of respiratory symptoms among production workers compared with non-production workers, reported the highest concentrations of respirable dust in the extrusion and curing areas of the facility [Attarchi et al 2013]. Rubber manufacturing emission exposure varies based on the type of rubber being produced; however, regardless of the type, rubber manufacturing workers can be exposed to mixture of numerous respiratory irritants in the form of gases, particles, and fumes [Akca et al 2011].…”
Section: Medical Surveymentioning
confidence: 99%
See 3 more Smart Citations